Optimization of Exhaust Emissions on FI Motorcycle using Programmable ECU and Ethanol Mixture with Taguchi Method - Purwanto Wawan; Firmansyah M. Sadly; Fajar Muhammad; Gunawan Akmal; Arif Ahmad; Sugiarto Toto; Putra Dwi Sudarno (E3S Web of Conferences)
This study investigates fluctuations in carbon monoxide (CO) and hydrocarbon (HC) levels in exhaust emissions from fuel-injected (FI) motorcycles equipped with programmable ECUs. For each test, three different injection and ignition timings are used, as well as three distinct spark plug types and three ethanol combinations. The study's goal is to determine the best settings for reducing exhaust emissions. This experimental study used the Taguchi method with the L9 orthogonal array, with FI motorcycles serving as the major research object. The most significant impact on emissions was found by ANOVA analysis to be injector timing (factor D), which contributed 52.90% for carbon monoxide and 25.21% for hydrocarbons. The optimum approach to lower exhaust emission levels is to use an iridium spark plug, 350° ATDC injector timing, 5° BTDC ignition timing, and gasoline-ethanol (E30), according to the results of the experimental verification. The findings provide valuable insights for optimizing engine settings to meet stricter environmental regulations and enhance fuel efficiency, contributing to sustainable and eco-friendly transportation solutions.